Use of 3D Models in the Surgical Decision-Making Process in a Case of Double-Outlet Right Ventricle With Multiple Ventricular Septal Defects - Shearn, Andrew I. U.; Yeong, Michael; Richard, Michael; Ordoñez, Maria Victoria; Pinchbeck, Henry; Milano, Elena G.; Hayes, Alison; Caputo, Massimo; Biglino, Giovanni (Frontiers in Pediatrics, 2019)
3D printing has recently become an affordable means of producing bespoke models and parts. This has now been extended to models produced from medical imaging, such as computed tomography (CT). Here we report the production of a selection of 3D models to compliment the available imaging data for a 12-month-old child with double-outlet right ventricle and two ventricular septal defects. The models were produced to assist with case management and surgical planning. We used both stereolithography and polyjet techniques to produce white rigid and flexible colour models respectively. The models were discussed both at the joint multidisciplinary meeting and between surgeon and cardiologist. From the blood pool model the clinicians were able to determine that the position of the coronary arteries meant an arterial switch operation was unlikely to be feasible. The soft myocardium model allowed the clinicians to assess the VSD anatomy and relationship with the aorta. The models, therefore, were of benefit in the development of the surgical plan. It was felt that the clinical situation was stable enough that an immediate intervention was not required, but the timing of any intervention would be dictated by decreasing oxygen saturation. Subsequently the oxygen saturation of the patient did decrease and the decision was made to intervene. A further model was created to demonstrate the tricuspid apparatus. An arterial switch was ultimately performed without the LeCompte manoeuvre, the muscular VSD enlarged and baffled into the neo aortic root and the perimembranous VSD closed. At one month follow up SO2 was 100%, there was no breathlessness and no echocardiogram changes.